Effect of ball milling on the catalytic conversion of cellulose to levulinic acid - Khan, A.S. (Trans Tech Publications Ltd, 2014)
The yield of levulinic acid from cellulose is very low because of a strong network of intera- and intermolecular hydrogen bonding. Ball milling cause significant decrease in the cellulose crystalinity and thus increase the production of levulinic acid (LA) by using Aluminum Chloride (AlCl3) as a catalyst. By means of AlCl3 depolymerization, cellulose can produce 5- Hydroxymethylfurfural (5-HMF) and subsequently LA. The effect of reaction temperature and time were investigated. The maximum yield of LA (36.5 mol ) was achieved using 180 Í¦C and 240 min. Â© 2014 Trans Tech Publications, Switzerland.